2020
DOI: 10.1021/acs.analchem.0c02203
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide Interrogation of Small GTPases Regulated by N6-Methyladenosine Modulators

Abstract: N 6-Methyladenosine (m6A) in messenger RNA (mRNA) regulates its stability, splicing, and translation efficiency. Here, we explored how the expression levels of small GTPase proteins are regulated by m6A modulators. We employed a high-throughput scheduled multiple-reaction monitoring (MRM)-based targeted proteomic approach to quantify systemically the changes in expression of small GTPase proteins in cells upon genetic ablation of METTL3 (the catalytic subunit of the major m6A methyltransferase complex), m6A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…To address this, we first investigated whether YTHDC2 regulates SLC7A1 1 mRNA. mRNA homeostasis is maintained by the “production-degradation” balance [ 33 , 34 ]. The YTH domain played no role in suppressing SLC7A11 promoter activity when YTHDC2 was overexpressed in H1299 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address this, we first investigated whether YTHDC2 regulates SLC7A1 1 mRNA. mRNA homeostasis is maintained by the “production-degradation” balance [ 33 , 34 ]. The YTH domain played no role in suppressing SLC7A11 promoter activity when YTHDC2 was overexpressed in H1299 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The m6A regulators inhibited melanoma development by increasing the methylation of Hint2 ( Jia et al, 2019 ). Yang et al revealed the positive/negative regulatory role for METTL3/ALKBH5 in RHOB and RHOC (a subset of small GTPase proteins) in melanoma ( Yang et al, 2020 ). YTHDF1 interferes with the presentation of dendritic cells by promoting the expression of lysosomal protease in dendritic cells and gives rise to disorder in the immune response.…”
Section: Introductionmentioning
confidence: 99%
“… 9 With the advance of m6A, the studies demonstrate that m6A and m6A associated proteins are involved in various biological and pathological processes, such as splicing, transport, translation and degradation. 10 , 11 In addition, the abnormal expression of m6A associated proteins are involved in regulating genes that impact cell processes and physiological function in various cancers. As Figure 1 shows, m6A modification is regulated by three types of proteins, including the m6A methyltransferase (“writer”), demethylase (“eraser”) and reading proteins (“reader”).…”
Section: Introductionmentioning
confidence: 99%